デザインは市場成果をもたらすのか? - 原 寛和; 立本 博文 (Akamon Management Review, 2018)
This paper reviews prior empirical studies on the effect of product design on firm performance, by classifying them into three areas: (i) firm level, (ii) product level and (iii) design organization level. These studies support product design positively affects firm performance through the complex mechanism with mediation and/or interaction effects. These empirical results suggest further studies regarding (1) strategic context and product design process, (2) consumer cognition as mediation variables between design process and firm performance and (3) organizational mechanisms and key factors in design management. 製品デザインが市場成果に与える影響について、(i)企業レベル(ii)製品レベル(iii)デザイン組織レベルに分類して実証研究のレビューを行なった。いずれの研究も、製品デザインが市場成果にプラスの影響を与えることを支持している。ただし、そのメカニズムは単純ではなく、変数間の媒介効果や交互作用効果を多く含んでいる。これら既存研究のレビューを踏まえ、今後の研究として、(1)戦略的文脈の影響を考慮した研究 (2)消費者の反応を取り込んだデザインプロセスの研究 (3)デザインマネジメントの組織メカニズムの研究が必要であることを報告する。